ANALISIS PERILAKU KONSUMEN DALAM KEPUTUSAN MENGGUNAKAN KOSMETIK HALAL DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERATING - Humaira, Humaira (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2023)
This study examines the factors of consumer behavior on decision making by Muslim women in the city of Medan on the use of wardah cosmetics. This study uses a quantitative descriptive method. When collecting the required data, the researcher will distribute questionnaires to the research samples. Related to this, the population of this study is all Muslim women in Medan City, and the research sample is Muslim women who are determined using the slovin formula. Where based on the calculations carried out with the formula, this study will use the responses of 100 Muslim women to a questionnaire that has been previously determined by the researcher. After getting responses from 100 samples, the researcher will recapitulate the data from the respondents. After that, the researcher will analyze the research data using the moderation regression method. The results showed that the variables of motivation, perception, and attitude influenced consumer decisions in using Wardah cosmetics. Religiosity as a moderating variable can only strengthen the influence of motivational variables on the decision to use Wardah cosmetics. This study proves that there is a need for information and education about halal and the benefits of a product, especially cosmetics so that Muslim women can determine which products are halal and suitable for consumption. It can also provide wider insight and knowledge regarding the variables that influence consumption behavior